Discogene Monothioscyllitol-Derivate - Bernd Kohne; Klaus Praefcke; Werner Stephan (CHIMIA)
Two derivatives (3 and 4) of the hitherto unknown 1-deoxy- 1-mercapto-scyllo-inositol (monothioscyllitol), a sulfur analogue of the naturally occurring scyllo-inositol, have been prepared by nucleophilic substitution reaction from a hexaester of myo-inositol (2). They are the first thermotropic discotic liquid crystalline compounds with an alicyclic saturated «core» and a non-centrosymmetric structure exhibiting strong dipole moments in benzene solution and wide mesophase ranges.